Analisis Perbandingan Konsepsi Ketuhanan dalam Al-Qur’an dan Bible - Esti Oktavya; Nurdin; Muh. Ikhsan; Fatira Wahidah; Muhammad Syahrul Mubarak (Gunung Djati Conference Series, 2022)
This study aims to discuss the comparison of the conception of God in the Qur'an and the Bible. This study uses an approach by applying the descriptive-analytical method. The formal object of this research is divinity in the Qur'an and the Bible. While the material object is the comparison of divinity in the Qur'an and the Bible. The results based on this discussion indicate that the comparison of the conception of God in the Qur'an and the Bible has a congruence of meaning with the parameters in the lexeme meaning God in the Qur'an and the semantic Arabic Bible in the Qur'an and the Bible. This study concludes that a comparison of the conception of divinity in the Qur'an and the Bible can be developed based on the instructions of the Qur'an, the Bible and the opinions of various figures.